PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN SALAK DI DESA NGARGOSOKO, KECAMATAN SRUMBUNG, KABUPATEN MAGELANG - Monica, Dhea Apta; Widowati, Nina; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2021)
ABSTRACT Community empowerment in Ngargosoko Village through salak processing training is an effort made to optimize the abundant salak resources. This study aims to analyze community empowerment in the management of salak in Ngargosoko Village, Srumbung District, Magelang Regency. This study used descriptive qualitative method. Sources of data in this study were obtained from interviews, observations, and documentation. The technique of selecting informants was carried out using purposive sampling and accidental sampling. This study uses the theory of the dimensions of empowerment success. The results obtained, namely the access aspect has been fulfilled and supports the implementation of empowerment. Aspects that do not support the empowerment carried out, namely participation, control, and welfare. Community participation is still lacking because they are reluctant to spend their time participating in training. Control in the form of monitoring and assistance is only carried out when the activity is ongoing, before and after the activity does not exist. In the aspect of the welfare of the people of Ngargosoko Village, in fulfilling the need for food and clothing, it is still not fully fulfilled if it only relies on the results of the salak harvest. The driving factor for the empowerment of salak in Ngargosoko Village is the abundant potential of salak resources and the high interest of the community in empowerment. The inhibiting factors for empowerment are commitment of training participants, lack of monitoring, and marketing of training products. Suggestions that can be given are to improve coordination between the agency and village government and collaborate with third parties in marketing training products.